Terrorismo y guerrilla : la violencia contra el Estado en Europa y América Latina : un análisis comparativo - Waldmann, Peter (Estudios Internacionales, 1992)
Are there similarities between the numerous and diverse acts of violence against the state that exist today in the West? Faced with this question, in this paper two models are distinguished: the guerrilla in Latin America and terrorism in Europe. To test this hypothesis, a typological scheme is made to analytically differentiate both concepts, which is then illustrated by two cases: the Red Army Faction (RAF) in the Federal Republic of Germany and Sandinismo in Nicaragua. Other examples are described and the various types are listed, analyzing the geopolitical context in which they occur. Finally, other mixed forms that do not fit into the aforementioned scheme are presented: European ethnic violence and Latin American urban guerrillas.